Silicon promotes the control of Meloidogyne incognita in lettuce by increasing ascorbic acid and phenolic compounds - de Souza Alonso, Tales Arthur [UNESP]; da Silva, Dalila Lopes [UNESP]; de Mello Prado, Renato [UNESP]; Soares, Pedro Luiz Martins [UNESP]; Tenesaca, Luis Felipe Lata [UNESP]; Ferreira, Rivanildo Júnior [UNESP] (Springer Nature, 2022)
Abstract: Silicon (Si) has a physical barrier effect on plant tissues, decreasing nematode infection in different crops. Notwithstanding, research on lettuce is lacking, especially regarding the chemical mechanisms of action of this beneficial element. This study evaluated the effect of Si supply on lettuce plants infested with 0, 6000, and 12,000 eggs and second stage juveniles of Meloidogyne incognita, both in the absence and in the presence of Si (2 mM) in the nutrient solution. Silicon increased phenolic compounds and ascorbic acid, reducing M. incognita population and decreasing oxidative stress. The element also increased chlorophyll content and the quantum efficiency of photosystem II (FV/FM), favoring lettuce growth and production. The use of Si decreased the number of nematodes and affected their reproduction, decreasing the number of eggs and galls on lettuce roots. This indicates that Si may serve as a sustainable alternative for the control of M. incognita. The benefit of using Si appears to be due to the combined effect chemical action from the increase in phenolic compounds and ascorbic acid in plant tissues, improving plant physiology. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Beneficial element; Biotic stress; Juveniles; Lactuca sativa; Phenols; Root-knot nematode